Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Komunikasi terhadap Kinerja Karyawan (Studi kasus PDAM Tirta Moedal Kota Semarang) - Brian Ardya Pandhega; Dian Prawitasari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Employee performance is a crucial factor in an organization’s success, including PDAM Tirta Moedal Semarang as a public service provider. However, the decline in employee performance remains an issue that requires serious attention. This study aims to examine the influence of leadership style, work environment, and communication on employee performance at PDAM Tirta Moedal Kota Semarang. The research employed a purposive sampling approach, with data collected through questionnaires from a sample of 88 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 24. The results indicate that leadership style, work environment, and communication have a positive and significant influence on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 43.3% suggests that these variables collectively explain a substantial portion of the variation in employee performance, while the remainder is influenced by other factors.